Communication as a Tool: Enhancing Financial Inclusion in Capital Market through Hybrid Learning - Parameshadila Zafirah Sandra Gunawan; Dewi Widowati; Dessy Puspitasari (Jurnal Komunikasi dan Bisnis, 2023)
The number of Indonesian capital market retail investors have been increasing in recent years. This trend shows a growing of investment opportunities, one of which is supported by the development of digital technology and enables individuals to access information to capital market with ease. However, based on the existing data shows a low level of financial literacy within the capital market, only 5%. Despite the increasement of the retail investors, there are still cases of investment fraud, with 5,523 reported complaints of investment fraud in Central Java. In response to this concern, PT Bursa Efek Indonesia provides free and open access for everyone through a comprehensive Sekolah Pasar Modal, organized by each Representative Office (Kantor Perwakilan) available in every province in Indonesia. Kantor Perwakilan BEI Jawa Tengah 1 conduced Sekolah Pasar Modal monthly and is carried out in a hybrid learning approach. This study is aimed to comprehensively and analyze the learning initiatives concerning capital market taught by Staff Trainer, analyzed using the Social Learning Theory, through the elements of Attention, Retention, Reproduction, and Motivation. This research is adopting a qualitative research, data collection is achieved by conducting interviews with the Staff Trainer and the Sekolah Pasar Modal’s offline and online participants, and observation during the learning process. The findings of this research were that the Staff Trainer provide numerous conceptual terms that resonates to the local culture resulted in a more relatable experience for the participants. Furthermore, it is found that the Staff Trainer frequently provides extrinsic motivation strategies during the learning process.